STUDENTS’ EXPERIENCES OF USING VLOG TO LEARN ENGLISH - Taqwa, Ananda; Sandi, Vernanda Nopita (Journal of Foreign Language Teaching and Learning, 2019)
There has been a change in the process of learning from a conventional way into the technologically-based way these days. From this change, it is necessary to find out the significance of utilizing technology in learning English from students? perspectives. This study aims to investigate the EFL students? experiences of using vlogs, as one of the technology products to learn English. In conducting this research, the researchers adopted exploratory study as the approach and employed the hermeneutic phenomenology as the research design. These designs have relations to description and interpretation of the meaning of EFL students? experience. One student participated in this study. The researchers employed the student?s reflection as part of the assignment after making vlogs as well as a one-on-one in-depth interview to obtain the data. At this point, two research questions are underlying this study, namely: (1) How are the students? experiences in learning English using vlogs?; (2) What does the student learn from it? From the data analysis, the researchers found several findings in this study. For the first research question, there are three findings found, namely, losing words to say, conveying English language expression, expressing his identity, looking for additional information in English. For the second research question, there are four findings revealed. Those were detailed guideline making, better editing, confidence gaining, and vocabulary improvement.